Adherence to Self-Care among Patients with Hypertension in Ethiopia: A Systematic Review and Meta-Analysis. (16th July 2022) - Edmealem, Afework; Ademe, Sewunet; Gedamu, Sisay
Abstract : Background . Self-care adherence for hypertensive patients is a cornerstone for the control of it and prevention of its complications. However, there are inconsistent findings for self-care adherence of hypertensive patients in Ethiopia. Thus, this systematic review and meta-analysis was done to determine the pooled estimate self-care adherence. Methods . This systematic review and meta-analysis was reported based on the Preferred Reporting Items for Systematic Review and Meta-Analysis guideline. An intensive search of online databases such as PubMed (MEDLINE), CINHAL, Google Scholar, and advanced Google search was made to access both published and unpublished articles that report self-care adherence among hypertensive patients in Ethiopia. The pooled estimate was done with STATA version 11 metan commands in a 95% confidence interval. The presence of heterogeneity and publication bias were detected by I 2 and Egger's test, respectively. A random-effect model was obtained, and subgroup analysis was done for the management of heterogeneity. Result . A total of 24 articles with a total of 7224 participants were included in the final systematic review and meta-analysis. The pooled estimate of overall self-care adherence among hypertensive patients was 36.98% (95% CI: 27.13–46.83). In subgroup analysis, the highest overall self-care adherence was observed in the Amhara region at 53% (95% CI: 46.54, 59.47). The pooled estimate of self-care dimensions such as medication adherence, low-salt diet, physical activity, smoking abstinence, alcohol abstinence, and weight management was 62.71%, 65.96%, 47.28%, 92.53%, 67.59%, and 52.54%, respectively. Conclusion . The pooled estimate of good self-care adherence among hypertensive patients was low. From the dimensions of self-care, the lowest level was in physical activity and the highest level was in smoking abstinence. Comparing all regions, the lowest level of overall self-care adherence was observed in Addis Ababa, Tigray region, and South Nations and Nationalities of Ethiopia. Screening of adherence to self-care and health education should be provided to every patient during every visit.